Standard-dose versus high-dose conformal radiotherapy with concurrent and consolidation carboplatin plus paclitaxel with or without cetuximab for patients with stage IIIA or IIIB non-small-cell lung cancer (RTOG 0617): a randomised, two-by-two factorial phase 3 study. Issue 2 (February 2015) - Bradley, Jeffrey D; Paulus, Rebecca; Komaki, Ritsuko; Masters, Gregory; Blumenschein, George; Schild, Steven; Bogart, Jeffrey; Hu, Chen; Forster, Kenneth; Magliocco, Anthony; Kavadi, Vivek; Garces, Yolanda I; et al.
Summary: Background: We aimed to compare overall survival after standard-dose versus high-dose conformal radiotherapy with concurrent chemotherapy and the addition of cetuximab to concurrent chemoradiation for patients with inoperable stage III non-small-cell lung cancer. Methods: In this open-label randomised, two-by-two factorial phase 3 study in 185 institutions in the USA and Canada, we enrolled patients (aged ≥18 years) with unresectable stage III non-small-cell lung cancer, a Zubrod performance status of 0–1, adequate pulmonary function, and no evidence of supraclavicular or contralateral hilar adenopathy. We randomly assigned (1:1:1:1) patients to receive either 60 Gy (standard dose), 74 Gy (high dose), 60 Gy plus cetuximab, or 74 Gy plus cetuximab. All patients also received concurrent chemotherapy with 45 mg/m 2 paclitaxel and carboplatin once a week (AUC 2); 2 weeks after chemoradiation, two cycles of consolidation chemotherapy separated by 3 weeks were given consisting of paclitaxel (200 mg/m 2 ) and carboplatin (AUC 6). Randomisation was done with permuted block randomisation methods, stratified by radiotherapy technique, Zubrod performance status, use of PET during staging, and histology; treatment group assignments were not masked. Radiation dose was prescribed to the planning target volume and was given in 2 Gy daily fractions with either intensity-modulated radiation therapy or three-dimensional conformal radiation therapy. The use of four-dimensional CT and image-guided radiation therapy were encouraged but not necessary. For patients assigned to receive cetuximab, 400 mg/m 2 cetuximab was given on day 1 followed by weekly doses of 250 mg/m 2, and was continued through consolidation therapy. The primary endpoint was overall survival. All analyses were done by modified intention-to-treat. The study is registered withClinicalTrials.gov, numberNCT00533949 . Findings: Between Nov 27, 2007, and Nov 22, 2011, 166 patients were randomly assigned to receive standard-dose chemoradiotherapy, 121 to high-dose chemoradiotherapy, 147 to standard-dose chemoradiotherapy and cetuximab, and 110 to high-dose chemoradiotherapy and cetuximab. Median follow-up for the radiotherapy comparison was 22·9 months (IQR 27·5–33·3). Median overall survival was 28·7 months (95% CI 24·1–36·9) for patients who received standard-dose radiotherapy and 20·3 months (17·7–25·0) for those who received high-dose radiotherapy (hazard ratio [HR] 1·38, 95% CI 1·09–1·76; p=0·004). Median follow-up for the cetuximab comparison was 21·3 months (IQR 23·5–29·8). Median overall survival in patients who received cetuximab was 25·0 months (95% CI 20·2–30·5) compared with 24·0 months (19·8–28·6) in those who did not (HR 1·07, 95% CI 0·84–1·35; p=0·29). Both the radiation-dose and cetuximab results crossed protocol-specified futility boundaries. We recorded no statistical differences in grade 3 or worse toxic effects between radiotherapy groups. By contrast, the use of cetuximab was associated with a higher rate of grade 3 or worse toxic effects (205 [86%] of 237 vs 160 [70%] of 228 patients; p<0·0001). There were more treatment-related deaths in the high-dose chemoradiotherapy and cetuximab groups (radiotherapy comparison: eight vs three patients; cetuximab comparison: ten vs five patients). There were no differences in severe pulmonary events between treatment groups. Severe oesophagitis was more common in patients who received high-dose chemoradiotherapy than in those who received standard-dose treatment (43 [21%] of 207 patients vs 16 [7%] of 217 patients; p<0·0001). Interpretation: 74 Gy radiation given in 2 Gy fractions with concurrent chemotherapy was not better than 60 Gy plus concurrent chemotherapy for patients with stage III non-small-cell lung cancer, and might be potentially harmful. Addition of cetuximab to concurrent chemoradiation and consolidation treatment provided no benefit in overall survival for these patients. Funding: National Cancer Institute and Bristol-Myers Squibb.